Review of solar dryers for agricultural products in Asia and Africa: an innovation landscape approach - Udomkun, Patchimaporn; Romuli, S.; Schock, S.; Mahayothee, B.; Sartas, Murat; Wossen, T.; Njukwe, E.; Vanlauwe, Bernard; Müller, J. (Elsevier, 2020)
Solar drying is one of the most efficient and cost-effective, renewable, and sustainable technologies to conserve agricultural products in Asian and sub-Saharan African (SSA) countries. This review paper presents the different types of solar dryers that are widely used in Africa and Asia. In addition, the pre-eminent effects of their use on product quality, as well as their economic, environmental, and social impacts, are highlighted. Since financial, external, and structural factors play a key role in the adoption and scaling of solar dryers, this paper also discusses the impact of these factors on the effectiveness of solar drying technologies in selected Asian and SSA countries.